BERSEDEKAH KEPADA PENGEMIS PERSPEKTIF HADIS NABI SAW - H. Rajab; Marlina Wally (TAHKIM, 2022)
Nowadays begging has been abused by some people as a profession so that the urge not to give "alms" to beggars on the streets, red lights, and other public places. Even in some places, this appeal will be endeavored to be upgraded to a regional regulation or other legal regulation. Begging in the perspective of the Prophet's hadith is forbidden and only allowed under three conditions, namely those who are in debt to repay their debts, people affected by disasters, such as crop failures, begging to meet their needs, until he has a business that can meet his basic needs, and people who are widely known as very needy people. The Prophet provide solutions so that beggars can try to overcome economic difficulties.Keywords: charity, beggars, hadith of the Holy Prophet, Islamic law.